2013
DOI: 10.1016/j.neubiorev.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of fMRI reward paradigms used in studies of adolescents vs. adults: The impact of task design and implications for understanding neurodevelopment

Abstract: The neural systems underlying reward-related behaviors across development have recently generated a great amount of interest. Yet, the neurodevelopmental literature on reward processing is marked by inconsistencies due to the heterogeneity of the reward paradigms used, the complexity of the behaviors being studied, and the developing brain itself as a moving target. The present review will examine task design as one source of variability across findings by compiling this literature along three dimensions: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
163
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(173 citation statements)
references
References 136 publications
(209 reference statements)
3
163
1
Order By: Relevance
“…Our study was not designed to decide between these different roles, but given that insula activation tracked increasing risks and greater activation was related to greater risk aversion (at least in adolescents), our results may be consistent with an (aversive) valuation of risk or increased perception of risk in adolescence (Rudorf et al, 2012). Subjective risk (and return) ratings in future studies may help to disentangle these accounts.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our study was not designed to decide between these different roles, but given that insula activation tracked increasing risks and greater activation was related to greater risk aversion (at least in adolescents), our results may be consistent with an (aversive) valuation of risk or increased perception of risk in adolescence (Rudorf et al, 2012). Subjective risk (and return) ratings in future studies may help to disentangle these accounts.…”
Section: Discussionmentioning
confidence: 65%
“…Though evidence has accumulated using simple reward paradigms, the current study takes a computational approach to break down complex, dynamic risky decisions into constituent features to isolate what, in particular, drives unique features of decisions of children and adolescents at the behavioral level, and asks how the developing brain might carry out such unique decision calculations. A risk-return approach has been applied and validated across many behavioral (Weber, 2010) and neuroeconomic studies in adults (Preuschoff et al, 2008;Tobler et al, 2009;Mohr et al, 2010a, b;Rudorf et al, 2012), but is new to developmental neuroimaging studies. By applying this riskreturn decomposition we were able to study the development of Indicates clusters also observed at the more peaked cluster-thresholding criterion Z Ͼ 2.6, p Ͻ 0.05; FWE cluster-corrected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported both increases and decreases in mid-adolescence, although this may depend also on task demands (Bjork et al, 2010;Galvan, 2010;Richards, Plate, & Ernst, 2013). In a prior study by Op de Macks et al (2011), which involved a subset of participants reported in this study, it was found that reward-related brain activation correlated positively with testosterone levels, in both boys and girls.…”
Section: Developmental Changes and Individual Differencesmentioning
confidence: 55%
“…1). The curvilinear relationship between reward sensitivity and age is also well documented in the developmental neuroscience literature, in which most (though not all) studies show that activation in the brain's reward centers is greater during adolescence than before or after (11). The lack of a relationship between self-reported hedonism and age in the van den Bos study (1) is compounded by the limited variability in scores on this subscale, unlike future orientation scores, which are predictably and linearly related to age (see figure 1D in ref.…”
mentioning
confidence: 68%